Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Aspects of the ecology of killer whale (Orcinus orca Linn.) groups in the near-shore waters of Sub-Antarctic Macquarie Island - Toby Travers; John van den Hoff; Mary-Anne Lea; Kris Carlyon; Ryan Reisinger; P. J. Nico de Bruyn; Margie Morrice (Polar Biology, 2018)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)